Changing Programs to Fit New Strategies : Some Lessons from Ukraine - Lawrence, David (World Bank, Washington, DC, 2012)
When International Finance Corporations (IFC's) advisory services strategy evolves, it can lead to major program changes. This requires good risk management, because clients, donors, government, partner organizations, and staff are affected. A good strategy, coupled with solid management and well-executed programs, can do a lot to increase IFC's effectiveness. But it's easy to slip up.